The Ministry of Industry, Trade and Small & Medium Projects Decree No. 461 of the Year 2015 = وزارة الصناعة والتجارة والمشروعات الصغيرة والمتوسطة قرار رقم 461 لسنة 2015 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic